Reappraisal on pharmacological and mechanical treatments of heart failure - Bo Liang; Yu-Xiu Zhao; Xiao-Xiao Zhang; Hui-Ling Liao; Ning Gu (Cardiovascular Diabetology, 2020)
Abstract Heart failure (HF) is a highly frequent disorder with considerable morbidity, hospitalization, and mortality; thus, it invariably places pressure on clinical and public health systems in the modern world. There have been notable advances in the definition, diagnosis, and treatment of HF, and newly developed agents and devices have been widely adopted in clinical practice. Here, this review first summarizes the current emerging therapeutic agents, including pharmacotherapy, device-based therapy, and the treatment of some common comorbidities, to improve the prognosis of HF patients. Then, we discuss and point out the commonalities and areas for improvement in current clinical studies of HF. Finally, we highlight the gaps in HF research. We are looking forward to a bright future with reduced morbidity and mortality from HF.